Adaptive Innovation Paradigm in Archipelagic Governance Analysis of Civil Servants' Perceptions in Pangkajene and Kepulauan Regency, Indonesia - Rusito, Rusito; Sonjaya, Trisna; Nugroho, Arif; Permana, Deni (Jurnal Manajemen Pelayanan Publik, 2025)
This study considered civil servants' perceptions of public service innovation in archipelagic governance contexts in Pangkajene and Kepulauan Regency, South Sulawesi. By adopting stratified random sampling, 121 civil servants from four island sub-districts completed a validated 57-item questionnaire measuring five innovation dimensions. The results revealed high innovation perceptions with distinctive characteristics differing from mainland technocratic paradigms. Community-Based Implementation Strategy scored highest, while Structural Challenge Management scored lowest, with significant differences across island types. Infrastructure access, position level, and service length were key predictors, explaining 54.7% of variance. Cluster analysis identified three typologies: Pragmatic Adapters, Community Innovators, and Balanced Practitioners. Comparative analysis showed large gaps in technology orientation and local wisdom integration versus expected mainland responses, indicating paradigmatic differences. Archipelagic civil servants developed systematic adaptive innovation approaches emphasizing flexibility, community collaboration, and relational outcomes over technological modernization. These findings confronted universal public management principles and suggest context-specific innovation policies are necessary for effective archipelagic governance.